„[…] a Wonderfully Secretive Life, Pulsating with some Otherworldly Meaning.” Melchior Wańkowicz and Birds - Wasąg, Magdalena (Porównania, 2025)
The article is interdisciplinary and cross-cutting in nature. Birds in the works of Melchior Wańkowicz have been interpreted as messengers of universal values linked to childhood memories. They signal the mystery of existence and initiate delight in the world. Specific species such as the willow grouse, for example, symbolise the uniqueness of the Borderlands. Crows, jays, bee-eaters, hawks, cuckoos, woodpeckers, grouse, black grouse and partridges hidden in Wańkowicz’s stories are signs of the Borderlands past and of the close relationship with man. The article therefore takes into account inquiries into the significance of birds as a Borderland idiom in Wańkowicz’s work, and in this context includes selected photographs of birds taken by Wańkowicz, held in the collection of the Adam Mickiewicz Museum of Literature in Warsaw. An attempt has also been made to show that, in a broader sense, bird characters also served Wańkowicz as a means of creative invention. Birds in the American reportages of the author of the trilogy W ślady Kolumba (In the Footsteps of Columbus) were identified as another important reference.